On the Projective Description of Weighted (LF)-Spaces of Continuous Functions - Catherine V. Komarchuk; Sergej N. Melikhov (International Journal of Mathematics and Mathematical Sciences)
We solve the problem of the topological or algebraic description of countable inductive limits of weighted Fréchet spaces of continuous functions on a cone. This problem is investigated for two families of weights defined by positively homogeneous functions. Weights of this form play the important role in Fourier analysis.